The Dissolution of Mind A Fable of How Experience Gives Rise to Cognition - Vilarroya, Oscar (Brill Book Archive Part 1, ISBN: 9789004472495, 2002)
This book presents an original thesis about the notion of sensory experience and of the mind's architecture, which is grounded in current trends in cognitive science and philosophy of mind. Presented in the form of a dialogue, the book explores some of the psychological and philosophical consequences that the author derives from his proposal.--